Polemik Manusia Perdana antara Tafsir al-Qur’an al-’Aqli dengan Teori Barat - Rosyid, Moh (HERMENEUTIK : Jurnal Ilmu al-Qur'an dan Tafsir, 2019)
Al Quran, as the source of inspiration for Muslims, and the concept of the first person according to Charles Darwin’s Evolution Theory, 1859, is worth a discussion. Al Qur’an does not present firm statement about Adam as the first person in the world. Presumably, there are three communities prior Adam: Banul Jan, Banul Ban and Ijajil. Confirmation of Adam as the first person was given by mufassir. According to Al Qur’an, human beings are flawless creations consist of body (jasad) and soul (ruh) from the beginning. It contradicts to Darwin’s theory saying that human beings have the same origin with simphanse. This paper presents three methods of Quranic interpretation concerning the first human being: tafsir bi ar-ra’yi, tafsir maudhu’i and tafsir muqorin.